Pengaruh pengetahuan perpajakan, kesadaran wajib pajak, dan kepercayaan masyarakat pada pemerintah terhadap kepatuhan wajib pajak dalam membayar Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) di Kecamatan Pasan Kabupaten Minahasa Tenggara - Gahung, Priska Claudia; Warongan, Jessy D. L.; Mintalangi, Syermi S.E. (Riset Akuntansi dan Portofolio Investasi, 2024)
Rural and Urban Land and Building Tax is tax on land and/or buildings owned, controlled and/or utilized by individuals or entities. Rural and Urban Land and Building Tax (or PBB-P2) is a type of central tax where most of the proceeds are handed over to local governments. This research aims to determine the influence of tax knowledge, taxpayer awareness and public trust in the government on taxpayer compliance in paying rural and urban land and building taxes in Pasan District, Southeast Minahasa Regency. The number of samples used was 98 respondents using a sample collection method, namely probability sampling, using a simple random sample technique collected through a questionnaire. The analytical method used is multiple linear regression analysis with the help of the SPSS 29.0 application. The results of this research show that tax knowledge, taxpayer awareness, and public trust in the government have a positive and significant effect on taxpayer compliance in paying rural and urban land and building tax in Pasan District, Southeast Minahasa Regency.